2012
DOI: 10.1111/j.1469-7610.2012.02540.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of autism spectrum disorder in Cornelia de Lange syndrome

Abstract: Background: The prevalence of Autism Spectrum Disorder (ASD) symptomatology is comparatively

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
65
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 44 publications
(99 reference statements)
7
65
0
Order By: Relevance
“…This was perhaps unsurprising since high levels of comorbidity with ADHD are also observed in idiopathic ASD (Simonoff et al 2008). There was also no evidence of group differences in the item measuring anxiety which is also a feature of some genetic disorders such as fragile X (Rogers et al 2001) and Cornelia de Lange syndrome (Moss et al 2012). Based on our study, it is possible that with fewer observed RRB's and better eye contact these children do not present in clinic as idiopathic ASD and hence more likely to be overlooked by clinicians.…”
Section: Discussionmentioning
confidence: 93%
“…This was perhaps unsurprising since high levels of comorbidity with ADHD are also observed in idiopathic ASD (Simonoff et al 2008). There was also no evidence of group differences in the item measuring anxiety which is also a feature of some genetic disorders such as fragile X (Rogers et al 2001) and Cornelia de Lange syndrome (Moss et al 2012). Based on our study, it is possible that with fewer observed RRB's and better eye contact these children do not present in clinic as idiopathic ASD and hence more likely to be overlooked by clinicians.…”
Section: Discussionmentioning
confidence: 93%
“…4, 6, 1618 Unadjusted comparisons of ASD symptom scores are also commonly made between children with ASD and children with other psychiatric disorders or genetic syndromes who differ significantly on these variables. 4, 5, 19 Furthermore, many studies assessing the relationships between ASD symptoms (or autistic traits) and other behavioral, genetic, and neurobiological variables do not carefully take into account phenotypic characteristics, such as age, IQ, or EBP, as potential confounding factors. 2022 These practices have potentially very serious consequences, as they increase the likelihood of drawing erroneous conclusions about associations between ASD symptoms and etiological mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Cornelia de Lange syndrome, which is caused by mutations in NIP-BL, SMC3, and X-linked SMC1A and HDAC8 genes, occurs with and without ASD diagnostic symptoms (Moss et al 2012). However, with or without ASD diagnostic symptoms, Cornelia de Lange syndrome involves ID, social anxiety, and mutism.…”
Section: Genetic Syndromic Asd Has Been Found With Varied Brain Impaimentioning
confidence: 99%